A Review of Content Standards as the Foundation of Learning in the 2013 Curriculum - Ihwani, Dhini; Eka wira; Abdurrahmansyah (The Future of Education Journal, 2025)
This study examines the critical role, structure, implementation, and challenges of the content standards as the foundation of learning in the 2013 Curriculum in Indonesia. A qualitative research method with a library research approach was used, involving the collection and analysis of data from various scholarly literature, educational books, official documents, and journal articles published between 2021 and 2025. The population consists of all relevant literature on the content standards of the 2013 Curriculum, with purposive sampling. Data analysis employed content analysis techniques to synthesize the main findings. The results indicate that the content standards play an essential role in directing the scope of material, learning outcomes, and the development of competencies in cognitive, affective, and psychomotor domains. However, there are challenges such as teacher readiness, regional disparities, and the relevance of the curriculum to 21st-century skills. The conclusion underscores the need for continuous improvement in educators' capacity, periodic policy evaluations, and the development of a collaborative curriculum that integrates technology and global demands. This study serves as a comprehensive foundation for policymakers, curriculum developers, and practitioners to enhance the quality of education in response to current and future challenges.